Safety and efficacy of radiotherapy combined with immunotherapy in limited-stage small cell lung cancer a single-arm meta-analysis and systematic review - Li Yu; Xinlin Yu; Cheng Ma; Xialin Zhang; Ran Cui (PLoS ONE, 2025)
Background Limited-stage small cell lung cancer (LS-SCLC) has a poor prognosis despite being potentially curable with standard concurrent chemoradiotherapy. The success of immune checkpoint inhibitors (ICIs) in extensive-stage SCLC has prompted investigation into combining immunotherapy with radiotherapy for LS-SCLC. This systematic review and single-arm meta-analysis aims to synthesize the evidence on this combined modality, providing pooled estimates of efficacy and safety to inform clinical practice and future trials. Methods Following PRISMA guidelines, we systematically searched PubMed, Embase, Cochrane Library, and Web of Science through July 2025 for studies evaluating radiotherapy combined with immunotherapy in patients with LS-SCLC. The primary outcomes analyzed included pooled objective response rate (ORR), median progression-free survival (mPFS), and median overall survival (mOS). Results Six studies, encompassing 487 patients, met the inclusion criteria. The pooled analysis demonstrated an ORR of 57.7% (95% CI: 24.9–90.5%), a weighted mPFS of 13.6 months (95% CI: 11.3–15.9 months), and a pooled mOS of 33.7 months (95% CI: 26.7–40.7 months). Grade 3−4 treatment-related adverse events occurred in 42.2% of patients. Subgroup analyses revealed that a concurrent treatment sequence yielded a significantly higher ORR compared to sequential approaches (77.6% vs. 65.2% for immunotherapy followed by radiation vs. 25.8% for radiation followed by immunotherapy). Radiation dose was also identified as a critical determinant of efficacy. Anti-PD-L1 agents showed a numerically higher ORR than anti-PD-1 agents (96.0% vs. 65.0%). Conclusion The combination of radiotherapy and immunotherapy is a promising therapeutic strategy for LS-SCLC, demonstrating encouraging efficacy outcomes that appear favorable compared to historical benchmarks for chemoradiotherapy alone. Optimizing treatment sequencing, particularly favoring a concurrent approach, is crucial for maximizing clinical benefit. These findings support further investigation in randomized controlled trials to confirm the value of this combined modality and to identify predictive biomarkers for patient selection.